One−Step Synthesis Strategy for a Platinum−Based Alloy Catalyst Designed via Crystal−Structure Prediction - Dengjie Yan; Lingxin Kong; Baoqiang Xu; Bin Yang (Molecules)
The industrial application of polymer electrolyte membrane fuel cells is limited by the high cost of platinum catalysts. In this study, we developed a one−step synthesis strategy for low−platinum alloy catalysts based on crystal−structure predictions. Using this method, we successfully prepared a low−platinum alloy catalyst, i.e., CaPt2, which exhibits the same structure as its theoretically predicted counterpart in a single step via arc melting. There was no hazardous waste emission during the preparation of the alloy catalyst. Electrons were successfully enriched on the surfaces of platinum atoms, and the electronic structures of the platinum atoms were adjusted. The migration of oxygen intermediates during oxygen reduction was determined via an extensive oxygen−intermediate adsorption site test. The reaction path for the oxygen reduction process was determined. Electronic−structure analysis revealed the interaction mechanism between the oxygen intermediate and the platinum atom on the catalyst surface. The incorporation of calcium atoms into the alloy catalyst effectively improved the adsorption/dissociation state of the oxygen intermediates on the catalyst surface. Meanwhile, the molar fraction of platinum atoms in the CaPt2 alloy catalyst reduced by 33%, thus decreasing the feedstock cost of the catalyst. The double reduction in raw materials and manufacturing costs is conducive to the popularization and application of alloy catalysts. This study provides a reference for the design and production of other functional catalysts.